Personality development and human relations - Avelino, Soledad E.; Sanchez, Custodiosa A. (Manila, Philippines : Rex Book Store, 1996)
Through this book, the young mind of adolescent student will come to self-awareness, self-exploration, and self-actualization of all facets of his personality -- physical, social, mental, emotional, spiritual and moral. The students will find this book easy to understand because of its simple language. The explanations and the situational illustrations are all within the comprehension level of college students.
I. Introduction -- II. Foundations of personalit -- III. Physical attributes of personality -- IV. Personality traits -- V. Psychological attributes of personality -- VI. Stress -- VII. Motivation -- VIII. Emotions and mental health -- IX. The Moral and spiritual aspects of personality -- X. Human relations -- XI. Leadership -- XII. Communication -- XIII. Good manners and decorum -- XIV. Personality measurement.
Includes bibliographical references and index.
Keywords: INTERPERSONAL RELATIONS